Evaluation of the Control Options of Bovine Tuberculosis in Ethiopia Using a Multi-Criteria Decision Analysis - Gutema, Fanta D.; Agga, Getahun E.; Makita, Kohei; Smith, Rebecca L.; Mourits, Monique; Tufa, Takele B.; Leta, Samson; Beyene, Tariku J.; Asefa, Zerihun; Urge, Beksissa; Ameni, Gobena (Frontiers in Veterinary Science, 2020)
Bovine tuberculosis (BTB) is a zoonotic bacterial infection caused by Mycobacterium bovis and is characterized by the development of granulomatous lesions in the lymph nodes, lungs and other tissues. It poses serious public health impacts and food security challenges to the agricultural sector in terms of dairy and meat productions. In Ethiopia, BTB has been considered as a priority disease because of its high prevalence in urban and peri-urban dairy farms. However, there has not been any national control program in the country. Thus, in order to initiate BTB control program in the country, information on control options is needed to tailor the best option for the Ethiopian situation. The objective of this study was to identify, evaluate and rank various BTB control options in Ethiopia using a multi-criteria decision analysis based on preference ranking organization method for enrichment evaluations (PROMETHEE) approach while accounting for the stakeholders' preferences. Control options were evaluated under two scenarios: with (scenario 1) and without (scenario 2) bacillus Calmette–Guérin (BCG) vaccination. Nine potential control options were identified that include combinations of three control options (1) test and slaughter with or without government support, (2) test and segregation, and (3) BCG vaccination. Under scenario 1, BCG vaccination, BCG vaccination and test and slaughter with partial compensation by government, and BCG vaccination and test and slaughter with full compensation by government were the top three ranked control options. Under scenario 2, test and slaughter with full compensation by government was the preferred control option, followed by test and segregation supported by test and slaughter with full government compensation, and test and slaughter with half compensation by government. Irrespective of the variability in the weighting by the stakeholders, the sensitivity analysis showed the robustness of the ranking method. In conclusion, the study demonstrated that BCG vaccination, and test and slaughter with full compensation by government were the two most preferred control options under scenarios 1 and 2, respectively. National level discussions were strongly recommended for further concretization and implementation of these control measures.